(untitled) (Bulletin of criminological association of Ukraine, 2023)
The article explores the personality of the offender as a key element of criminalistic characteristics of child sexual abuse attempts, one of the most acute and pressing issues of modern times. It highlights that the relevance of the topic is driven not only by the increasing number of such crimes, including the involvement of children in the production of child pornography, but also by the transnational nature of these acts, which have spread due to the active use of internet technologies. It emphasizes that criminalistic characteristics are not only a system of information about the crime but also a practical tool for law enforcement officers, enabling them to propose hypotheses, plan investigative actions, evaluate evidence, and predict offender behavior. Special attention is given to the correlations between elements of criminalistic characteristics, which give it predictive significance. The article identifies key characteristics: adulthood (predominantly aged 18–35), often informal employment, which may indicate an asocial lifestyle or a desire to avoid supervision. It also stresses the possession of psychological manipulation skills, allowing the offender to establish "trusting" relationships with the child, exploiting vulnerabilities such as loneliness, low self- esteem, or the need for attention to persuade them toward further exploitation. Significant attention is paid to the active use of internet technologies and social media for searching and establishing contacts with children. Typical features include a tendency toward asocial behavior and/or deviant sexual preferences (pedophilia), manifesting, for instance, in the collection of child pornography or prior episodes of abuse. The article reveals a tendency for meticulous concealment and trace elimination, including the use of encrypted communication channels, disposable accounts, and specialized software. It particularly emphasizes that such individuals often choose professions or fields of activity that ensure constant and close contact with children (coaches, teachers, caregivers, volunteers), granting them unimpeded access to potential victims. It is also noted that such abuse can be either isolated crimes or components of organized criminal activities, where offenders act in collaboration with clear role distribution (groomers, operators, distributors, financiers, technical support).